2021
DOI: 10.1186/s12909-021-02803-8
|View full text |Cite
|
Sign up to set email alerts
|

Readiness towards online learning among physiotherapy undergraduates

Abstract: Background Online learning is an attractive option for educators, especially as means of overcoming the challenges posed by the global pandemic. Although it is best to evaluate student readiness prior to commencement of an online course, to ensure successful development and delivery of student-centric teaching and learning strategies, readiness towards online learning among physiotherapy undergraduates is unknown. The main aim of this study was to examine physiotherapy undergraduates’ readiness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
1
15
1
4
Order By: Relevance
“…Unlike the current study, other studies didn't show gender differences in online learning readiness (42)(43)(44)(45). Other studies reported that females were found to be more ready than males (30,46).…”
Section: Sociodemographic Factorscontrasting
confidence: 81%
“…Unlike the current study, other studies didn't show gender differences in online learning readiness (42)(43)(44)(45). Other studies reported that females were found to be more ready than males (30,46).…”
Section: Sociodemographic Factorscontrasting
confidence: 81%
“…From the triangulation model, undergraduates experienced academic stressors, either mild or moderate stress and this contributed to musculoskeletal pain. One of the reasons was their expectation that the classes were not as they thought they would be and their readiness for the new method was questionable [ 34 , 35 ]. One participant claimed that she felt overwhelmed with the topics, and some claimed that the amount of assignments doubled compared to the face-to-face teaching method.…”
Section: Discussionmentioning
confidence: 99%
“…To able these benefit of online learning more and more institutions are introducing online learning (Daniel, 2020). However, the introduction of such online courses must involve an examination of the attitudes of the stakeholders, i.e., the students and teachers (Ranganathan et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, in the context of the worldwide online learning revolution, it has become pertinent for BOU to shift some of its programs from conventional face-to-face to fully online courses. However, the launching of any such online courses must require a positive attitude from the stakeholders i.e., the students and teachers (Ranganathan et al, 2021). In this regard, to introduce online teacher education courses, this study is designed to explore the attitude of the students and faculty members of the School of Education towards online courses.…”
Section: Introductionmentioning
confidence: 99%